Concept Understanding Skill of 8th Grade Junior High School Students in Missouri Mathematics Project Learning Based Curiosity With Scaffolding - Rakhim, Ari Annisa; Kartono, Kartono; Supriyadi, Supriyadi (Universitas Negeri Semarang, 2021)
This study aims to describe the concept understanding of 8th grade students at various levels of student curiosity in learning the Missouri Mathematics Project with the Scaffolding approach based on diagnostic assessments. The research method used is a concurrent embedded type mix method. The population was taken from 8th grade students at SMP N 5 Pati. Subjects were chosen based on each category of level of curiosity. This category consists of high, medium and low using purposive sampling to determine the sample. The findings show that the understanding of concepts from various categories of curiosity has diverse understanding of concepts. Each category of curiosity can apply the concept or algorithm to solve the problem properly. So curiosity does not absolutely influence the ability to understand concepts.